Soft-Tissue Chondroma of Anterior Gingiva: A Rare Entity - Dhana Lakshmi Jeyasivanesan; Shameena Pazhaningal Mohamed; Deepak Pandiar (Case Reports in Dentistry)
Soft-tissue chondroma is a rare, benign, slow-growing tumor made up of heterotopic cartilaginous tissue. It occurs most commonly in the third and fourth decades in the hands and feet. Oral soft-tissue chondromas are uncommon and soft-tissue chondroma of gingiva is extremely uncommon. Here, we report an unusual case of soft-tissue chondroma of gingiva in a 50-year-old woman.